Investigation Study of Three-Level Cascaded H-bridge Multilevel Inverter - Mohd Ruddin Ab Ghani; Nabil Farah; Jurifa Lazi; M.R. Tamjis; Md Nazri Othman; Nur Huda Mohd Amin; Syariffah Othman; Zanariah Jano; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper analyzed three-level Cascaded H-bridge Multilevel Inverter (CHMLI) utilizing two modulation techniques namely Sinusoidal Pulse Width Modulation (SPWM) and Space Vector Pulse Width Modulation (SVPWM). The performance and the output of CHMLI in terms of Total Harmonic Distotion (THD) % and circuits complexity were compared. The simulations models were constructed using MATLAB/SIMULINK. The results showed the CHMLI produced the lowest THD contents and utilized fewer components. Moreover, the SVPWM produced less THD than SPWM.